1994
DOI: 10.1128/jb.176.10.2976-2985.1994
|View full text |Cite
|
Sign up to set email alerts
|

Novel surface attachment mechanism of the Streptococcus pneumoniae protein PspA

Abstract: Pneumococcal surface protein A (PspA) of Streptococcus pneumoniae has been found to utilize a novel mechanism for anchoring to the bacterial cell surface. In contrast to that of surface proteins from other gram-positive bacteria, PspA anchoring required choline-mediated interactions between the membrane-associated lipoteichoic acid and the C-terminal repeat region of PspA. Release of PspA from the cell surface could be effected by deletion of 5 of the 10 C-terminal repeat units, by high concentrations of choli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
0
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(212 citation statements)
references
References 67 publications
(63 reference statements)
6
198
0
4
Order By: Relevance
“…Even in the presence of 1 % choline, which should elute any LytA attached to TA and LTA in the pneumococcal cell wall, no band corresponding to LytA could be identified on the Western blots. This negative result is in accordance with data published by Yother & White (1994), who concluded that LytA is probably an intracellular protein. As we applied a very sensitive detection system for His-tagged proteins, and concentrated our supernatant samples 70-fold, our assay must be considered significantly more sensitive than the one employed by Yother & White (1994).…”
Section: Discussionsupporting
confidence: 93%
“…Even in the presence of 1 % choline, which should elute any LytA attached to TA and LTA in the pneumococcal cell wall, no band corresponding to LytA could be identified on the Western blots. This negative result is in accordance with data published by Yother & White (1994), who concluded that LytA is probably an intracellular protein. As we applied a very sensitive detection system for His-tagged proteins, and concentrated our supernatant samples 70-fold, our assay must be considered significantly more sensitive than the one employed by Yother & White (1994).…”
Section: Discussionsupporting
confidence: 93%
“…Depending on the number of repeats in the choline-binding domain, the CBPs are more weakly or strongly attached to the surface of the bacterium as well as an absolute requirement for substrate binding. This property has been shown for both PspA and LytA (Sanchez et al, 1990;Lopez et al, 1992;Garcia et al, 1994;Yother and White, 1994).…”
Section: Discussionmentioning
confidence: 55%
“…To evaluate the presence of SsEno in different bacterial compartments, S. suis strain 1669 was grown overnight at 37 uC with agitation in 30 ml THB. The subcellular components (supernatant, cell wall, cytoplasmic and membrane fractions) were fractionated with mutanolysin by using the method of Yother & White (1994). Equivalent amounts of all fractions were analysed by SDS-PAGE (12.5 % polyacrylamide) and Western blotting using optimally diluted rabbit anti-SsEno IgG.…”
Section: Methodsmentioning
confidence: 99%